Evaluation of cellulase-compatible ionic liquids for in situ hydrolysis and bioethanol production from oil palm empty fruit bunch (EFB) - Elgharbawy, Amal A. M. (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Ionic liquids (ILs) are green solvents that are able to reconstruct the lignocellulose structure for accessibility of cellulases in the hydrolysis process. This study aims to create a potential IL and cellulase integrated system in a single reactor to achieve a high ethanol yield from EFB. Cellulase (PKC-Cel) was derived from Trichoderma reesei (RUTC30) and displayed a promising stability in several ILs. In choline acetate [Cho]OAc, PKC-Cel retained 63.2% of the initial activity after six hours and lost only 10% of its activity in 10% IL/buffer solution. Upon the confirmation of the PKC-Cel stability, EFB was subjected to an IL-pretreatment followed by hydrolysis without the IL removal. The findings showed that [Cho]OAc and choline butanoate [Cho]Bu were the best ILs used since a higher sugar concentration was obtained after 24 hours compared to other ILs. In contrast with the untreated EFB, the amount of reducing sugar after the enzymatic hydrolysis increased by 3-fold in case of [Cho]OAc and [Cho]Bu, 2-fold with [EMIM]OAc and phosphate-based ILs whereas the lowest concentration was obtained in phosphonium-based IL. Significant differences in the morphology of EFB sample; before and after the treatment with [Cho]OAc and [Cho]Bu, were observed with SEM. Analysis showed that the total lignin content of raw EFB was reduced from 23.6±0.6 %(w/w) to 16.8±0.35 %(w/w) after the employment of [Cho]OAc in the compatible IL system. Based on our findings, the optimum conditions to obtain 79.4±0.96 g/l of reducing sugar (RS), equivalent to 0.62 ±0.06 g/ g EFB, were identified by applying Definitive Screening Design (DSD) and Response Surface Methodology (RSM). This represents around a 100% conversion of the theoretical cellulose content of the EFB to simple sugars and 38% of the lignocellulose to glucose. The EFB hydrolysate was evaluated as a potential media for ethanol production. The results obtained showed that the hydrolysate could be utilized without supplements. Furthermore, it was demonstrated that furfurals and TPC did not suppress the ethanol production by yeast. In addition, it was observed that crystallinity of the treated EFB reduced and the swelling increased which made the structure accessible by the cellulase enzyme. Three parameters were subjected to optimization by faced centered central composite design (FCCCD) for ethanol production. The center points of the design gave the highest ethanol concentration with an adequate agreement between the predicted (32.58±1.00 g/l) and experimental values (34.09 g/L) respectively. Based on the obtained results, the optimum process parameters were determined at a reducing sugar concentration of 70 g/L, an inoculum concentration of 5.5% (v/v) and an agitation of 170 rpm. The content of the distilled ethanol was 98.6% (v/v). The kinetics of the hydrolysis revealed that the IL resulted in a non-competitive mixed inhibition in which K_m increased and V_max reduced compared to the reaction in the absence of the IL. Monod's equation was used to describe the yeast growth and bioethanol production kinetics. The values of growth and non-growth associated constants proved that the bioethanol formation and sugar consumption were growth associated. Based on the observation, ethanol yielded 91.73% of the theoretical yield and 0.275 g ethanol/ g EFB. In conclusion, the IL-cellulase integrated system introduced in this study shows the development of the process in obtaining a high recovery of the bioethanol, however, more development is required to recover both the cellulase and the ionic liquid for several uses.